Wave identification in upward annular flow - a focus on ripple characterization. (April 2021) - Fershtman, Adam; Barnea, Dvora; Shemer, Lev
Highlights: A modified zero crossing technique for wave identification and height calculation was proposed. New criteria for differentiating between ripples and disturbance waves. Detailed statistical analysis of ripples, including wave height, velocity and length. Effect of azimuthal angle and pipe inclination on the interfacial structure of annular flow. Abstract: The interfacial structure of annular flow in upward inclined pipes is examined experimentally by a non-intrusive multilayer conductance liquid film sensor ( LFS ). In horizontal and inclined pipes, cross-sectional distribution of gas and liquid phases is asymmetric even on average. Thus, the ratio between the characteristic film thickness and the mean dominant wave parameters may vary significantly as a function of the azimuthal and inclination angles. Interface structure in upward annular flow is characterized by two kinds of waves, ripples and disturbance waves. An interface dominated by consecutive large amplitude disturbance waves may also contain numerous ripples. To differentiate between ripples and disturbance waves, a criterion based on statistical wave properties is required. Identification of individual waves is carried out using a zero-crossing procedure with a new reference value. This approach allows to identify both small and large amplitude waves at the interface, calculating the wave heights based on their individual crest and trough. The wave height probability density function ( pdf ) for a wave system consisting of ripples and disturbance waves is bimodal, with the first peak representing ripples and the second disturbance waves. The local minima between the two peaks in the pdf defines the boundary between ripples and disturbance waves for each flow condition and azimuthal angle. The clear differentiation of the two kinds of waves allows to focus on detailed description of the statistical properties of ripples that are presented as a function of the pipe inclinations angles (ranging from near horizontal to vertical) and for all azimuthal location across the pipe circumference.